2020
DOI: 10.17352/2455-815x.000060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage container and storage period on germination of grain maize in bako, West Shewa, Ethiopia

Abstract: Grain quality is in terms of heritably and physically pure whereas postharvest managements are used to increase grain/seed quality through seed processing while required storage condition maintain its quality. However, little information available on germination capacity of maize as affected by storage containers and period in Ethiopia. Thus, the aim of the study was to evaluate the effects of storage containers with storage period on germination of maize grain in the laboratory. The experiment was conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Poorly handled seeds during storage results in low performance in the field that results in lower production output that will be affecting food security. Unfavorable storage conditions and duration of the storage have an impact, which lowers the germination potential of seeds at some point [9]. Most research have confirmed that decrease in germination percentage from 5.0-10.0 % if wheat was sowed right after harvest and 5-17% decrease from seed stored grain approximately for 5 months.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poorly handled seeds during storage results in low performance in the field that results in lower production output that will be affecting food security. Unfavorable storage conditions and duration of the storage have an impact, which lowers the germination potential of seeds at some point [9]. Most research have confirmed that decrease in germination percentage from 5.0-10.0 % if wheat was sowed right after harvest and 5-17% decrease from seed stored grain approximately for 5 months.…”
Section: Literature Reviewmentioning
confidence: 99%